The contributions and difficulties of nursing in the prevention of cervical cancer: a literature review (Research, Society and Development, 2022)
Objective: To analyze the scientific literature on the prevention of cervical cancer in Brazil and discuss the difficulties of nursing professionals to carry out actions to prevent the disease. Methodology: This is an integrative review, carried out on the basis of Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and Scientific Electronic Library Online (SCIELO), articles written in the Portuguese language, published between 2017 and 2021. Results: A total of 334 articles were identified, after applying the inclusion and exclusion criteria, 17 articles were selected, 9 articles in LILACS, 5 in BDENF and 3 in SCIELO. The analysis of the articles used was done in a descriptive way and predisposed the stage of data extraction: author's name, year of publication, title and general objective of the study. Conclusion: Based on the results found, it is concluded that cervical cancer is a serious public health problem in Brazil, with the professional nurse being one of the main responsible for the organization of care in prevention, and it is extremely important to know the symptoms, diagnosis and treatment.